Staphylococcus aureus Infection Risk in a Population of Health Sciences Students at a Public University - Norhidayah MAT AZIS; Amielia AB HAMID; Hui Ping PUNG; Putri 'Amirah ABDUL RAFEE; Farizatul Akmawati YAHYA; Syafinaz AMIN NORDIN; Vasanthakumari NEELA; Zarizal SUHAILI; Mohd Nasir MOHD DESA (Tehran University of Medical Sciences, 2015)
Background: This study was undertaken to evaluate Staphylococcus aureus carriage and persistence in health sciences students at the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia. Methods: Consent form and self-administered questionnaires on socio-demographics, hygienic practices, medical and medication history were distributed followed by nasal swab collection; sampling was done twice in one month interval in October and November 2013. Bacterial identification followed the standard phenotypic methods. Antibiotic susceptibility of isolates against oxacillin and cefoxitin was tested by disc diffusion method. Methicillin resistance determinant gene (mecA) was detected through polymerase chain reaction-assay. Results: S. aureus was isolated from 31.3% (60/192) and 33.3% (60/180) of the student population during the first and second sampling respectively. Among the S. aureus-positive participants, about 65% of them were persistent carrier (S. aureus was detected during both sampling exercises). Six methicillin-resistant S. aureus (MRSA) were detected (four and two isolates in the two sampling events respectively) as inferred by decreased susceptibility to oxacillin and cefoxitin and presence of mecA gene; two of the strains were from a single individual. Fisher's exact test showed no significant correlation between carriage and the tested risk factors except for the habit of touching nose and chronic illnesses (P < 0.05), with a higher incidence of S. aureus among those associated with the two risk factors. Conclusions: As far as the limited sampling period is concerned, these findings indicate that a proportion of the student population may be at infection risk. Avoiding frequent nose-touching could be one of the preventive measures.   Keywords: Staphylococcus aureus, Infection risk, Nasal carriage, MRSA